PENAWARAN TEH HERBAL (Tisane) BAWANG DAYAK DI KELURAHAN JAHAB KECAMATAN TENGGARONG - Drianti, Astik (Jurnal Magrobis, 2019)
The objectives of this study is to determine supply equation and supply elasticity from dayak onion tisane.  This tisane supply equation is Y = 28,4175.X1 0,581741.X20,156042.X30,838484 with 60% significant factor on models. Supply elasticity 0,581741 and complementary relation with lemon grass tisane. Keywords : Tisane, Dayak Onion, Supply